2006
DOI: 10.3109/2000-1967-057
|View full text |Cite
|
Sign up to set email alerts
|

Radial Nerve Palsy at the Elbow

Abstract: We studied the clinical features and images along with surgical findings of 8 cages of radial nerve palsy due to a space-occupying lesion (SOL) at the elbow. Based on image findings, we examined compressing masses and their extent, we contrasted them with operative findings of the radial nerve, and we surmised the site of impairment. Compressing masses were ganglions in 6 cages, an old radial head dislocation in 1 case, and engorged radial recurrent vessels in 1 case. The extent of the SOLs was roughly 15-40 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…A ganglion cyst in the supinator muscle was reported, which caused compression of the posterior interosseous nerve leading to weakness of wrist extensors [10] . Matsubara et al reported 8 cases of radial nerve palsy due to ganglions at the elbow, with majority of cases presenting no symptoms [11] . Though the cyst was in close proximity with ulnar nerve, we did not find any evidence of compressive neuropathy in our case.…”
Section: Discussionmentioning
confidence: 99%
“…A ganglion cyst in the supinator muscle was reported, which caused compression of the posterior interosseous nerve leading to weakness of wrist extensors [10] . Matsubara et al reported 8 cases of radial nerve palsy due to ganglions at the elbow, with majority of cases presenting no symptoms [11] . Though the cyst was in close proximity with ulnar nerve, we did not find any evidence of compressive neuropathy in our case.…”
Section: Discussionmentioning
confidence: 99%
“…A ganglion cyst in the supinator muscle was reported, which caused compression of the posterior interosseous nerve leading to weakness of wrist extensors [ 10 ]. Matsubara et al reported 8 cases of radial nerve palsy due to ganglions at the elbow, with majority of cases presenting no symptoms [ 11 ]. We did not find any evidence of any compressive neuropathy in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Yamazaki reported 14 patients presenting with incomplete paralysis of the extensors of the wrist and fingers due to a ganglion at the elbow, located proximal to the arcade of Frohse in 13 cases and distal in 1, all causing PIN palsy [ 3 ]. Matsubara et al reported eight cases of radial nerve palsy due to ganglions at the elbow proximal to the arcade of Frohse, with compression of the deep and superficial branches seen in three cases, although paraesthesia was noted in only one of the cases, the others presenting with either no symptoms or heaviness of the elbow [ 4 ]. Bowen and Stone reported a ganglion in the supinator muscle involving compression of the posterior interosseous nerve causing an extensor weakness in the wrist [ 5 ].…”
Section: Discussionmentioning
confidence: 99%